Prevalence of ocular abnormalities in adults with Down syndrome in Hong Kong. Issue 4 (1st February 2013) - Fong, Angie Hon Chi; Shum, Jennifer; Ng, Alex L K; Li, Kenneth K W; McGhee, Sarah; Wong, David
Abstract : Background/aims: This was a cross-sectional survey to find the prevalence of visual impairment and eye diseases among adults with Down syndrome (DS) in Hong Kong. Methods: 91 DS patients over the age of 30 were recruited through the Hong Kong Down Syndrome Association. Each patient was provided with a complete ophthalmological assessment including best corrected visual acuity, refraction, slit lamp and fundus examination. Results: In our sample, 56.6% had normal vision to mild vision impairment, 33.7% and 7.2% had moderate and severe vision impairment, respectively, and 2.4% were blind. The mean presenting distant LogMAR visual acuity was 0.66 (Snellen equivalent 20/90), and the best corrected LogMAR visual acuity was 0.48 (Snellen equivalent 20/60). Significant refractive errors were found in 86.3% of the eyes, with spherical equivalent corrections ranging from −23.25D to +3.00D. Myopia and astigmatism were prevalent and found in 59.3% and 72.7% of the eyes, respectively. Blepharitis and chalazion were found in 44% of the eyes, while corneal problems were present in 27.5%. There were low incidences of infective keratitis (0.5%), keratoconus (0.5%) and Brushfield spots (1.1%). Cataracts were found in 72.2% of the eyes; 26.1% were congenital and 44.9% were age-related. Fundal abnormalities were present in 49.5% of the eyes. Conclusions: There is a high prevalence of vision impairment among Chinese DS adults. Uncorrected refractive errors, high myopia and cataracts are the main visually debilitating ophthalmological abnormalities. Vision may be improved through the simple use of glasses and early treatment of age-related cataracts.